(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The paper deals with the possibilities of implementing dynamic tariff regulation of on-street parking spaces in the capital city of Prague. Achieving optimal results is conditioned by the implementation of advanced technologies, but at the same time, the dynamic tariff regulation must follow the applicable legislation and, above all, be accepted by drivers. For this reason, the paper briefly discusses the technical and legislative possibilities of implementation, and most attention is paid to the conducted survey of user needs. The survey investigates the impact of parking prices on drivers’ motivation to park their vehicles in the area.